Body condition for the Sudrunskaya Reindeer Herd, 1995 -Sitsev data - Sitsev, Ivan (Polar Data Catalogue, 2015)
These data include quantitative measurements of reindeer body size and body condition indicators, listed in Summary below. The reindeer in this sample were collected by shooting, and measurements were taken post-mortem. Spatial data, i.e. latitude/longitude coordinates exist for the general locations of the collections.